Reflections on the Suffix Conjugations in Semitic - Loesov, Sergey (Journal of Semitic studies, 2022)
Suffix conjugations (SCs) of East and West Semitic may not be traced back to the same verb form in Proto-Semitic. Rather, they evolved separately, by way of a ‘common drift’ in the two branches of Semitic. This is demonstrated, in particular, by a crass contrast, both in forms and diathetic meanings, between the SCs of East and West Semitic. Due to the scarcity of data, a gapless reconstruction of diachronic paths for neither of the two branches is possible. Only one thing remains certain: both the SC in East Semitic and non-passive forms of the SC in Central Semitic ultimately came about via verbalisation of adjectives, first primary and then deverbal ones.